Analisis Implementasi Metode Fuzzy Tsukamoto Dalam Penentuan Calon Legislatif - Salim, Stanley; -, Sutrisno; Laia, Yonata; Ompusunggu, Elvis sastra; Barus, Ertina Sabarita; Sihombing, Oloan (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Being elected as a legislative candidate is a challenging matter. Of course, you must know in the field of politics, both locally and globally, qualified leadership attitudes, moral values, and integrity, financially and financially established in order to carry out campaigns and have a base of followers so that all visions and programs can be conveyed to the public as a whole and clearly. Voters are also required to be wiser and more selective in choosing quality legislative candidates, given that the eligibility rate of candidates in Indonesia is still relatively low, and many participants still need to meet the criteria as ideal legislative candidates. Therefore, a technology and support system is needed that can sort and help the general public in determining quality candidates; in this case, the Tsukamoto Fuzzy method is used, which can be a solution in providing competent candidate recommendations because it has the characteristics of shortening time and simplifying the selection process objectively. This fuzzy method is a support system that is very